Red Plant Oxford Reading Tree - Hunt, Roderick; illustration, Alex Brychta (Oxford University Press, 1987)
Red Planet" is a book from the Oxford Reading Tree series, aimed at young readers. The story follows a group of children who embark on an exciting adventure. They are transported to Mars, the Red Planet, where they encounter strange and new experiences. As they explore the alien environment, the children work together to solve problems and face various challenges. The book introduces readers to the concept of space exploration in a fun and engaging way, blending adventure with educational elements about space. Through the characters' interactions and discoveries, young readers learn about teamwork, problem-solving, and curiosity.
Keywords: Teacher Resource English fiction story